New centralities in medium-sized cities: analysis of the subcenters of the Tomba and Cidade Nova districts in Feira de Santana, Bahia - Cerqueira, Lilian da Mota Silva; Santos, Janio Laurentino de Jesus (Revista Cerrados, 2024)
The objective of this article is to analyze the changes in urban centrality in Feira de Santana due to the consolidation of subcenters and to reflect on the alterations triggered by this process in its urban and economic dynamics, through the investigation of the Tomba and Cidade Nova districts. The methodology was based on bibliographic studies to provide a theoretical framework of the center, decentralization, and subcenters; fieldwork including the survey of tertiary establishments in the studied areas, data collection through interviews, and application of qualitative-quantitative questionnaires on the Google Forms platform, as well as the development of land use and occupancy maps and flow maps. The subcenters of Tomba and Cidade Nova can be considered the main expressions of centrality outside the central area of Feira de Santana, due to the diversity of tertiary activities that they offer and the decentralization experienced by the city. The emergence of new centralities affects the role of the Traditional Center, which was once considered the sole polarizing nucleus of the city and which now, due to changes in urban centrality, tends to relatively lose this role.